Stigma and chronic illness: A comparative study of people living with HIV and/or AIDS and people living with hypertension in Limpopo Province, South Africa - Erhabor S. Idemudia; Matthew O. Olasupo; Mantwa W. Modibo (AOSIS, 2018)
Background: Stigma among people with chronic illnesses exists, preventing many sufferers from presenting for treatment especially in South Africa. Objectives: This study compared stigma experiences of people living with human immunodeficiency virus and/or acquired immunodeficiency syndrome (HIV and/or AIDS) (PLWHA) and people living with hypertension (PLWHPT) in Limpopo Province of South Africa. Method: Using a cross-sectional design, 600 participants (300 PLWHA with mean age of 31 years, standard deviation of 8.2; and 300 PLWHPT with age of 55 years, standard deviation of 8.1) were purposefully sampled at HIV and/or AIDS and hypertension outpatient clinics. The perceived stigma of AIDS scale was used to assess stigma in the HIV and/or AIDS sample while the adapted version was used to assess stigma in PLWHPT. Data were analysed using independent t-test. Results: Results indicated that PLWHA experienced significantly higher enacted stigma (t(598) = −11.79, p < 0.001) as compared to PLWHPT. However, PLWHPT experienced significantly higher internalised stigma (t(598) = 37.56, p < 0.001) and perceived stigma (t(598) = 41.71, p < 0.001) than PLWHA. Conclusion: Stigma among people with chronic illnesses is existent. The stigma type is, however, dependent on the nature of the illness. Stigma reduction interventions among these populations are indicated.